Planned organisational change and organisational commitment-to-change: the moderating role of leader-member exchange - Cheong, Kah Chun; Lo, May Chiun; Abang Azlan, Mohamad; Ramayah, T. (2023)
This study aims to explore the relationship between planned organisational change and organisational commitment-to-change and how would leader-member exchange moderates the relationship in regards to change readiness, valences and perception of change. Organisational change is a complex process and the behavioural responses of employees towards the change are rather complicated. Despite the complexity, not much research has been conducted to show how these variables are related to each other. One hundred eighty-four respondents from the financial industry of Malaysia had participated in this study. Based on the nature and characteristics of this research the SmartPLS method was used. Surprisingly, the results of planned organisational change and organisational commitment-to-change show different implications as compared to past research but leader-member exchange remains as the determinant in moderating the relationship between the two variables. In conclusion, the findings of this research create a new path for the study of an approach, unlike others.